Association of vitamin D deficiency and subclinical diabetic peripheral neuropathy in type 2 diabetes patients - Sun, Xiaoyang; Yang, Xinyu; Zhu, Xiaopeng; Ma, Yu; Li, Xu; Zhang, Yuying; Liu, Qiling; Fan, Chenmin; Zhang, Miao; Xu, Binger; Xu, Yanlan; Gao, Xin; et al. (Frontiers in Endocrinology, 2024)
Background: Diabetic peripheral neuropathy (DPN) contributes to disability and impose heavy burdens, while subclinical DPN is lack of attention so far. We aimed to investigate the relationship between vitamin D and distinct subtypes of subclinical DPN in type 2 diabetes (T2DM) patients.: This cross-sectional study included 3629 T2DM inpatients who undertook nerve conduction study to detect subclinical DPN in Zhongshan Hospital between March 2012 and December 2019. Vitamin D deficiency was defined as serum 25-hydroxyvitamin D (25(OH)D) level < 50 nmol/L. Results: 1620 (44.6%) patients had subclinical DPN and they were further divided into subgroups: distal symmetric polyneuropathy (DSPN) (n=685), mononeuropathy (n=679) and radiculopathy (n=256). Compared with non-DPN, DPN group had significantly lower level of 25(OH)D (P < 0.05). In DPN subtypes, only DSPN patients had significantly lower levels of 25(OH)D (36.18±19.47 vs. 41.03±18.47 nmol/L, P < 0.001) and higher proportion of vitamin D deficiency (78.54% vs. 72.18%, P < 0.001) than non-DPN. Vitamin D deficiency was associated with the increased prevalence of subclinical DPN [odds ratio (OR) 1.276, 95% confidence interval (CI) 1.086-1.501, P = 0.003] and DSPN [OR 1. 646, 95% CI 1.31-2.078, P < 0.001], independent of sex, age, weight, blood pressure, glycosylated hemoglobin, T2DM duration, calcium, phosphorus, parathyroid hormone, lipids and renal function. The association between vitamin D deficiency and mononeuropathy or radiculopathy was not statistically significant. A negative linear association was observed between 25(OH)D and subclinical DSPN. Vitamin D deficiency maintained its significant association with subclinical DSPN in all age groups. Conclusions: Vitamin D deficiency was independently associated with subclinical DSPN, rather than other DPN subtypes.